Reading poetry, writing genre : English poetry and literary criticism in dialogue with classical scholarship - Bär, Silvio; Hauser, Emily (Fiction writer) (Bloomsbury studies in classical reception, 2018)
"This volume connects the situatedness of genre in English poetry with developments in classical scholarship, exploring how an emphasis on the interaction between English literary criticism and Classics changes, sharpens, or perhaps even obstructs views on genre in English poetry. 'Genre' has classical roots: both in the etymology of the word and in the history of genre criticism, which begins with Aristotle. In a similar vein, recent developments in genre studies have suggested that literary genres are not given or fixed entities, but subjective and unstable (as well as historically situated), and that the reception of genre by both writers and scholars feeds back into the way genre is articulated in specific literary works. Classical scholarship, literary criticism, and genre form a triangle of key concepts for the volume, approached in different ways and with different productive results by contributors from across the disciplines of Classics and English literature. Covering topics from the establishment of genre in the Middle Ages to the invention of female epic and the epyllion, and bringing together the works of English poets from Milton to Tennyson to Josephine Balmer, the essays collected here argue that the reception and criticism of classical texts play a crucial part in generic formation in English poetry"--